Technology Teachers as Researchers
VIII, 310 p.
Keywords: This book presents the scientific output of the TUFF research school in Sweden. In this school, a group of active teachers worked together on a series of educational research studies. All of those studies were related to the teaching about technology and engineering. The research program consisted of studies at various angles of view: a philosophical view, a national view, and a classroom practice view. The book is a showcase of how a well-conducted research program for teachers can lead to good contributions to technology education research. A selection of topics: the nature of technological knowledge, mental images of engineers and engineering, the process of choosing for a study in technology, teachers’ beliefs about technology education and assessment. These topics are directly related to major issues in the international technology education research agenda. The studies presented here were the basis of the authors’ Ph.D. theses. The teachers’ chapters are preceded by a description of ideas behind the TUFF research school and the way it was realized.